1994
DOI: 10.2140/pjm.1994.165.17
|View full text |Cite
|
Sign up to set email alerts
|

The structure of sl(2,1)-supersymmetry: irreducible representations and primitive ideals

Abstract: We give a detailed study of the enveloping algebra of the Lie superalgebra sl(2, 1), including classification of irreducible HarishChandra modules, completeness of finite dimensional irreducible, explicit computation of center, and classification of primitive ideals.Introduction and main results. Lie superalgebras are important both in physics and in mathematics [5]. In physics, they are used e.g. to unify fermions and bosons in a unique picture (one irreducible representation of the structure) via supersymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In section 6, we present complete sets of representations corresponding to infinite subsets of the set of continuous parameters. All the representations of these complete sets have the same dimension, unlike in the classical case [1]. Finally, in section 7, we prove the relations in the centre using our complete set of irreducible representations.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In section 6, we present complete sets of representations corresponding to infinite subsets of the set of continuous parameters. All the representations of these complete sets have the same dimension, unlike in the classical case [1]. Finally, in section 7, we prove the relations in the centre using our complete set of irreducible representations.…”
Section: Introductionmentioning
confidence: 87%
“…This terminology was used in [1], where the authors found complete sets of finite dimensional irreducible representations of the classical sl(2) and sl(2|1). For quantum groups at roots of unity, we shall obtain rather different results.…”
Section: Complete Sets Of Representations Of U Q (Sl(2))mentioning
confidence: 99%
See 1 more Smart Citation
“…they satisfy the classical analogues of (20,21). The relations (14,15,16,22,23,24) are still valid as long as the indices p i are greater or equal to 2. Notice that the classical operators Q (±) p , C p and S p are not the limits as q goes to 1 of the corresponding quantum ones, but rather limits of some linear combinations of them (See [8]).…”
Section: Another Examplementioning
confidence: 96%
“…In Sections 7 and 8, we describe A Λ (n) and A λ (n) using the enveloping algebra U of the Lie superalgebra osp (1,2) and its primitive quotients [20]. Denoting by A λ the algebra A λ (0), one has:…”
Section: Introductionmentioning
confidence: 99%